The association between the inflammatory potential of diet and the risk of histopathological and molecular subtypes of breast cancer in northwestern Iran: Results from the Breast Cancer Risk and Lifestyle study. Issue 12 (7th April 2022) - Hayati, Zahra; Montazeri, Vahid; Shivappa, Nitin; Hebert, James R.; Pirouzpanah, Saeed
Abstract : Background: This study explored the association between diet‐associated inflammation and the risk of different molecular subtypes of breast cancer (BrCA) in a large, population‐based case‐control study conducted in northwestern Iran. Methods: The study consisted of 1007 women with histopathologically confirmed BrCA and 1004 controls admitted to hospitals in Tabriz, northwestern Iran, for nonneoplastic conditions. Dietary Inflammatory Index scores and energy‐adjusted Dietary Inflammatory Index (E‐DII) scores, with and without supplements, were computed on the basis of dietary intake collected using a validated 136‐item food frequency questionnaire. Results: Women with the highest E‐DII scores (quartile 4) versus those with the lowest E‐DII scores (quartile 1) showed a significantly increased BrCA risk (odds ratio for quartile 4 vs quartile 1 [ORQ4vsQ1 ], 1.87; 95% confidence interval [CI], 1.42‐2.47), particularly for lobular carcinoma (ORQ4vsQ1, 3.07; 95% CI, 1.34‐7.02). Findings were similar for premenopausal women diagnosed with luminal A BrCA (ORQ4vsQ1, 2.71; 95% CI, 1.74‐4.22) or luminal B BrCA (ORQ4vsQ1, 2.86; 95% CI, 1.39‐5.89). Women consuming the most proinflammatory diets were 3 times more likely to have triple‐negative BrCA (ORQ4vsQ1, 3.00; 95% CI, 1.002‐8.96) while compared to luminal A BrCA. The BrCA risk for women consuming diets in the highest half of E‐DII scores (E‐DII > 0) was 59% greater than the risk for those in the lowest half (95% CI, 1.29‐1.97). Also, higher E‐DII scores that took into account supplements were associated with larger tumor sizes (T3 > 5 cm; P < .05). Conclusions: A proinflammatory diet, as indicated by higher E‐DII scores, appears to increase the risk of BrCA in Iranian women. Large increases in risk were seen in invasive molecular subtypes of BrCA. Anti‐inflammatory diets are suggested to prevent the risk of overall BrCA and more aggressive forms of BrCA in particular. Abstract : A proinflammatory diet appears to increase the risk of breast cancer (BrCA) in Iranian women. Large increases in risk were seen for invasive molecular subtypes of BrCA (ie, the triple‐negative and HER2‐enriched BrCA subtypes).